DOES CANDIDATE OF SCIENCES NEED TO PUBLISH ARTICLES? - Valery A. Gurtov; Lyudmila V. Shchegoleva (Высшее образование в России)
The article presents the results of analysis of publication activity of applicants for Candidate of science degree, in 2 years before and after thesis defense of. In 2013, an applicant had in average 13 publications, among them 11 were articles including three in Enumeration of Higher Attestation Commission (VAK Enumeration). About half among those who defended thesis in 2010, were registered in eLIBRARY.RU resource. During the following years (2011-2014) 35% of those who have got the Candidate degree diplomas did not publish any articles registered in Russian Science Citation Index. Only 10% of candidates of science still continue an active research activities including writing articles.